Pekerja Anak - Abang Ishar (PSGA LP2M IAIN Pontianak, 2019)
Every born child should have adequate nurture and care in terms of security, safety, wealth, and education. The parents’ responsibilities, even, are not only feeding meals, giving the security, giving the happiness, and so on, but also more than those things. Furthermore, the responsibility of caring the children relates to presenting them spiritual and religious values in life. That is the reason, moreover, why children are the gifts of God and very precious, even their values could not be retrieved by money, power, or magnificent palaces. The children’s existence for parents is somehow could not be resisted; they are gifts, generations, and investments for parents. Thus, one of the marriage goals is to gain incredible children; that children are being exploited to be workers saddens every parent in the world, in fact.